The Combined Effects of Warming and Body Size on the Stability of Predator-Prey Interactions - Kratina, Pavel; Rosenbaum, Benjamin; Gallo, Bruno; Horas, Elena L.; O’Gorman, Eoin J. (Frontiers in Ecology and Evolution, 2022)
Environmental temperature and body size are two prominent drivers of predation. Despite the ample evidence of their independent effects, the combined impact of temperature and predator-prey body size ratio on the strength and stability of trophic interactions is not fully understood. We experimentally tested how water temperature alters the functional response and population stability of dragonfly nymphs (Cordulegaster boltonii) feeding on freshwater amphipods (Gammarus pulex) across a gradient of their body size ratios. Attack coefficients were highest for small predators feeding on small prey at low temperatures, but shifted towards the largest predators feeding on larger prey in warmer environments. Handling time appeared to decrease with increasing predator and prey body size in the cold environment, but increase at higher temperatures. These findings indicate interactive effects of temperature and body size on functional responses. There was also a negative effect of warming on the stability of predator and prey populations, but this was counteracted by a larger predator-prey body size ratio at higher temperatures. Here, a greater Hill exponent reduced feeding at low prey densities when predators were much larger than their prey, enhancing the persistence of both predator and prey populations in the warmer environment. These experimental findings provide new mechanistic insights into the destabilizing effect of warming on trophic interactions and the key role of predator-prey body size ratios in mitigating these effects.